Localization Analysis of Natural Toxin of Solanum tuberosum L. via Mass Spectrometric Imaging - Hashizaki, Riho; Komori, Hanaka; Kazuma, Kohei; Konno, Katsuhiro; Kawabata, Kyuichi; Kaneko, Daisaku; Katano, Hajime; Taira, Shu (International Journal of Biotechnology for Wellness Industries, 2016)
The use of mass spectrometry imaging (MSI) revealed the localization of a-solanine and a-chaconine as natural toxins for Potato (Solanum tuberosum L.). The content of Potato glycoalkaloids, a-solanine and a-chaconine, were quantitatively determined by high performance liquid chromatography (HPLC). Matrix assisted laser desorption/ionization-based tandem mass spectrometry (MS) could determine a-solanine and a-chaconine from raw potato extraction and section. After budbreak, a-solanine and a-chaconine were produced and localized at periderm and germ compared with that before budbreak. At germ region, these glycoalkaloids did not exist whole germ region but eccentrically localize at germ surface and central region. The amount of a-chaconine was twofold higher than a-solanine at periderm. At germ region, there was no difference between these toxins.